Note on pointwise contractive projections - L. M. Sanchez Ruiz; J. R. Ferrer Villanueva (International Journal of Mathematics and Mathematical Sciences)
Let C(X) be the space of real-valued continuous functions on a Hausdorff completely regular topological space X. endowed with the compact-open topology. In this paper necessary and sufficient conditions are given for a subspace of C(X) to be the range of a pointwise contractive projection in C(X).